THE FILLING OF PRATAMA HIGHER LEADERSHIP POSITIONS TO STRENGTHEN BUREAUCRACY REFORM IN THE PERSPECTIVE OF PERFORMANCE RESPONSIBILITY OF THE STATE CIVIL APPARATUS IN BATAM CITY COVERNMENT - Fadlan; Zudan Arif Fakrulloh; Faisal Santiago (Faculty of Law, Universitas Gadjah Mada, 2023)
Abstract The purpose of this article is to analyze the position of the Regulation of the Minister for Empowerment of State Apparatus and Bureaucratic Reform (Menpan-RB) Number 13 of 2014 concerning Procedures for Filling High Leadership Positions in the Hierarchy of Legislation, and to criticize the mechanism and implementation of the fulfillment process of the Primary Leadership Position (JPT) and building a Bureaucratic Model used by the State Civil Apparatus (ANS) to promote the Performance Accountability Perspective to improve Good Governance and Clean Government. In order to answer the aim of the study, we used a combination of the normative